Grey matter volume differences of textual memorization: a voxel based morphometry study - Sapuan, Abdul Halim; Mustofa, Nur Shahieda; Che Azemin, Mohd Zulfaezal; Abdul Majid, Zafri Azran; Jamaludin, Iqbal (Springer Singapore, 2016)
Textual memorization involves intensive memorization techniques and processes, including repetition, rehearsal, and retrieval. Yet, little is known about the possible effects of this robust memorization training on brain structures. Therefore, this study was designed to investigate the presence of structural plasticity in the brain, which may develop after long-term practice of textual memorization techniques. The subjects are a group of huffaz who underwent one year of textual memory training. Twenty-eight volunteers (14 males) were enrolled in this study. Brain images of the subjects were obtained by employing 1.5 Tesla MRI and 3D-MPRAGE imaging sequence. Voxel-based morphometry was applied to assess the gray matter volume differences in the memorizers and the control subjects. The current study found that gray matter volume in the anterior cingulate gyrus, orbitofrontal cortex, left inferior temporal gyrus, right occipitotemporal gyrus, left inferior parietal gyrus, right perirhenal cortex, superior parietal cortex, posterior cingulate cortex and anterior cingulate cortex of the memorizers were significantly increased as compared with the control subjects. The results suggest textual memorization involves with extensive connection across the brain.